1992
DOI: 10.1677/jme.0.0080087
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid residue replacement in the β subunit of human chorionic gonadotrophin results in the loss of biological activity

Abstract: The heterodimer, human chorionic gonadotrophin (hCG), contains an alpha subunit that is common to the glycoprotein hormones and a hormone-specific beta subunit. A comparison of all known beta amino acid sequences shows that an aspartic acid at position 99 (with the numbering scheme for hCG-beta) is one of the seven non-Cys invariant residues. Using site-directed mutagenesis we have replaced hCG-beta Asp99 with Arg. Chinese hamster ovary cells, containing a stably integrated gene for bovine alpha subunit, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Based on results from our laboratory the minimum structural requirements of this region for receptor binding activity seem to be the Cys residue at 93 and 100 and net positive charge. The importance of this region as such, and several critical residues in it, for receptor binding have also been shown using chimeric and mutagenesis approaches by other groups (26–31).…”
Section: Discussionmentioning
confidence: 99%
“…Based on results from our laboratory the minimum structural requirements of this region for receptor binding activity seem to be the Cys residue at 93 and 100 and net positive charge. The importance of this region as such, and several critical residues in it, for receptor binding have also been shown using chimeric and mutagenesis approaches by other groups (26–31).…”
Section: Discussionmentioning
confidence: 99%
“…By homologous modelling, Willey and Leidenberger (1989) suggested that, for hCG, Ser-38 and His-83 on the a-subunit formed a similar active site with the j3-subunit Asp-99, the latter being the only conserved aspartic acid residue in all reported j3-subunit sequences (Bousfield et al, 1987). Recently, Chen and Puett (1992) changed the hCG 13-subunit Asp-99 to an arginine residue by sitedirected mutagenesis.…”
Section: Theoretical Tertiary and Quaternary Modelsmentioning
confidence: 99%
“…By homolo¬ gous modelling, Willey & Leidenberger (1989) sug¬ gested that, for hCG, Ser38 and His83 on the a-subunit formed a similar active site with the ß-subunit Asp99, this being the only conserved aspartic acid residue of all reported ß-subunit sequences ). Recently, Chen & Puett (1992) changed the hCG ß-subunit Asp99 to an arginine residue by site-directed mutagenesis.…”
Section: Detection and Measurement Of Hcgmentioning
confidence: 99%